Thermal and exergy analysis of solar air collectors with passive augmentation techniques - Ucar, A.; Inalli, M. (Pergamon-Elsevier Science Ltd, 2006)
One of the main disadvantages of solar air collectors in practical applications is their relatively low efficiency In this experimental investigation, the shape and arrangement of absorber surfaces of the collectors were reorganised to provide better heat transfer surfaces suitable for the passive heat transfer augmentation techniques. The performance of such solar air collectors with staggered absorber sheets and attached fins on absorber surface were tested. The exergy relations are delivered for different solar air collectors. It is seen that the largest irreversibility is occurring at the conventional solar collector in which collector efficiency is smallest. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: solar air collectors; thermal efficiency; exergy loss